Analysis of Stock Valuation and Business Performance of a Digital Media Company in Indonesia Before and After the Covid-19 Pandemic (Case Study: Global Mediacom) - Imaduddin, Aufarizqi; Rahadi, Raden Aswin (Green Publisher Indonesia, 2023)
The rise of digital streaming and investing in Indonesia has been exacerbated by the COVID-19 pandemic. One company involved in this unprecedented scenario is PT Global Mediacom TBK (BMTR). The everchanging digital streaming landscape and its massive growth create both an opportunity and threat for the company’s growth. The study aims to analyse stock valuation and performance of digital media in Indonesia pre-pots pandemic. To analyse this, the study utilized secondary data from the company’s annual report and various secondary sources. The data is processed using absolute valuation method of Discounted Cash Flow valuation and relative valuation method of Price-to-Earnings Ratio, Price-to-Book Value and EV/EBITDA. Using the absolute valuation method, it is found that the company’s stock is currently overvalued with an intrinsic value of Rp 169 in comparison to the actual price of Rp 278. One of the reasons for this is the company’s high beta stock of 1.8 which could signal a higher risk but higher return. Using the relative valuation method, all the metrics found that BMTR stock is undervalued. Being constantly below the industry average. However, the financial analysis as well as the relative valuations has found that the company is the most stable out of all the Indonesian listed digital streaming companies. This demonstrates the excellent business performance of the company.